2014
DOI: 10.1073/pnas.1321171111
|View full text |Cite
|
Sign up to set email alerts
|

Selection and constraint underlie irreversibility of tooth loss in cypriniform fishes

Abstract: The apparent irreversibility of the loss of complex traits in evolution (Dollo's Law) has been explained either by constraints on generating the lost traits or the complexity of selection required for their return. Distinguishing between these explanations is challenging, however, and little is known about the specific nature of potential constraints. We investigated the mechanisms underlying the irreversibility of trait loss using reduction of dentition in cypriniform fishes, a lineage that includes the zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 41 publications
0
41
2
Order By: Relevance
“…The mixed direction of effects of benthic alleles could alternatively result from pleiotropy (35), with QTL controlling other adaptive benthic phenotypes that might secondarily affect tooth patterning. For example, the large-effect toothspacing QTL on chromosome 4 overlaps the Ectodysplasin (Eda) gene which controls adaptive reductions in armor plate patterning (36) and is also well known to affect vertebrate tooth patterning (37,38). Interestingly, Eda also plays a role in the spacing of hair placodes and tooth cusps in mice (39,40), making Eda an excellent candidate for underlying the tooth-spacing QTL on chromosome 4.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed direction of effects of benthic alleles could alternatively result from pleiotropy (35), with QTL controlling other adaptive benthic phenotypes that might secondarily affect tooth patterning. For example, the large-effect toothspacing QTL on chromosome 4 overlaps the Ectodysplasin (Eda) gene which controls adaptive reductions in armor plate patterning (36) and is also well known to affect vertebrate tooth patterning (37,38). Interestingly, Eda also plays a role in the spacing of hair placodes and tooth cusps in mice (39,40), making Eda an excellent candidate for underlying the tooth-spacing QTL on chromosome 4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both oral and pharyngeal tooth formation require Ectodysplasin signaling (reviewed in Sadier et al, ). Furthermore, ectopic expression of Ectodysplasin is remarkably sufficient to restore dorsal pharyngeal tooth formation in zebrafish (Aigler et al, ). A previous study found evidence for the conservation of a dental gene network between oral and pharyngeal teeth in two species of cichlids, M. zebra and L. fuelleborni (Fraser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Modularity of the dentition can be seen across vertebrate lineages, as in Cypriniformes such as zebrafish, which have uncoupled tooth patterning in the dorsal and ventral pharynx, completely losing dorsal pharyngeal teeth while retaining ventral pharyngeal teeth (Stock, 2007). In zebrafish, the addition of a single transgene driving ubiquitous Ectodysplasin is sufficient to drive the formation of ancestrally lost dorsal pharyngeal teeth (Aigler et al, 2014). In mice, strong support for genetic modularity of the dentition has also been found.…”
Section: Distinct Genetic Bases Underlie Convergently Evolved Tooth Gainmentioning
confidence: 99%